Frontispiece: Monitoring the Discontinuous Dodecamer–Icosamer Transition of a Calix[4]arene‐Derived Surfactant by Time‐Resolved Small‐Angle X‐ray Scattering. Issue 24 (6th June 2017) - Takahashi, Rintaro; Matsumoto, Sakiko; Fujii, Shota; Narayanan, Theyencheri; Sakurai, Kazuo
Abstract : Calixarenes Micelles based on calixarene surfactants undergo a transition from dodecamers into icosamers upon an increase in the NaCl concentration, which was directly observed by time‐resolved SAXS as described by K. Sakurai et al. in their Communication onpage 6734 ff.